Lead with your customer transform culture and brand into world-class excellence - Jones, Mark David; Kober, J. Jeff (ATD Press, 2019)
Your one-stop shop for world-class results The most admired organizations in the world have the same basic resources that you have--offices, computers, pencils, pens, phones, Internet, people. The primary difference is the way they use those resources. How do successful organizations consistently succeed? We witness their extraordinary results, but the secrets often remain hidden. In Lead With Your Customer, authors Mark David Jones and J. Jeff Kober offer the key success tools all world-class organizations have in common and explain how your organization can adopt them. To understand their customer-first approach, they offer the World Class Excellence Model--the result of decades of success as leaders at the Walt Disney Company and years of experience and research working with over two dozen Fortune 500 companies. The authors explain how "world class" status can be attained by many organizations, and isn't the domain of only the most expensive, luxurious, or popular brands. Jones and Kober guide you by detailing benchmark practices and illustrating how they are followed by all best-in-class organizations by viewing each person inside and around the organization as your "customer"--Internally, as you engage your employees and build your organization's culture, and externally, as you engage your customers and build your brand. For this second edition, the authors present updated examples from organizations including IKEA, Harley-Davidson, Southwest Airlines, Ritz-Carlton, MD Anderson Cancer Center, and, of course, Walt Disney
Previous edition published: 2010. - Includes bibliographical references. - Online resource; title from title page (Safari, viewed April 17, 2019)
Keywords: Leadership; Customer services; Corporate culture; Success in business; Organizational Culture; Service à la clientèle; Culture organisationnelle; Succès dans les affaires